Intergroup Attitudes: School Counselors' Experiences Regarding the Attitudes of Turkish and Syrian Primary School Classmates towards each other - Abbas Türnüklü; Fulya Türk; Mustafa Tercan; Tarkan Kaçmaz (Anı Publishing, 2020)
The purpose of this study was to analyze the attitudes of Turkish and Syrian elementary school classmates towards each other within the framework of school psychological counselors' experiences. The study was carried out utilizing a phenomenological approach which is one of the qualitative research approaches. Semi-structured interview technique was used to collect data. The data were collected by interviewing a total of 40 school psychological counselors (8 males, 32 females). Qualitative data were analyzed using thematic analysis technique. As a result of the research, the prevalent themes that are effective in the development of Turkish and Syrian elementary school classmates' attitudes towards each other were found to be their sharing the same classroom, the common language and communication capabilities, intergroup contact and friendship, feelings of acceptance / belonging, exclusion and being excluded, perceived superiority, in-group solidarity, self-esteem, academic performance, teacher behaviors, and students' families' reactions against the out-group. Within this context, it can be concluded that planning and implementing mixed activities in and out of the classroom that would engage Turkish and Syrian students and allow them to have contact is likely to help develop positive intergroup attitudes.